Serum miR-9 as a prognostic biomarker in patients with osteosarcoma - Fei, Dan; Li, Yang; Zhao, Dongxu; Zhao, Kaijun; Dai, Lu; Gao, Zhongli (Journal of international medical research, 2014)
Objectives To quantify microRNA-9 (miR-9) concentrations in the serum of patients with osteosarcoma; to explore its relationship with clinicopathological characteristics and prognosis of osteosarcoma. Method Serum miR-9 was quantified via real-time reverse transcription–polymerase chain reaction in patients with osteosarcoma and healthy control subjects. Overall survival was evaluated using the Kaplan–Meier method. Results Serum miR-9 was significantly upregulated in patients with osteosarcoma (n = 118) compared with healthy control subjects (n = 60); its upregulation was significantly associated with advanced tumour–node–metastasis stage, larger tumour size and presence of distant metastasis. Overall survival duration was significantly shorter in patients with relatively high miR-9 concentrations compared with those with relatively low miR-9 concentrations. Conclusions Serum miR-9 concentrations are significantly increased in patients with osteosarcoma compared with healthy controls. Upregulation of miR-9 is associated with tumour stage, size and metastasis. Serum miR-9 quantification may represent a useful diagnostic and prognostic marker of osteosarcoma.